The Effect of Tobacco Smoking on Gingival Crevicular Fluid Volume - Üstün, Kemal; Ö. Alptekin, Nilgün (European Journal of Dentistry, 2007)
Objectives: The negative effects of smoking on periodontal health are well known. But the mechanism is not clear yet. The aim of the present study is to investigate the effects of smoking on gingival crevicular fluid (GCF) volumeMethods: The study included 26 age and gender matched periodontally healthy males. Half of the participants were smokers and the others were non-smokers. After periodontal measures were taken GCF samples were collected from 4 teeth of the subjects. The GCF volume was measured with an electronical deviceResults: The mean plaque index (PI) and gingival crevicular fluid (GCF) volumes were significantly lower in non-smokers (P=.019 and P=.027, respectively). The other parameters did not show significant differencesConclusions: Smoking significantly increased GCF volume compared to non-smoking subjects. This may contribute to the negative effects of smoking on periodontal tissues. (Eur J Dent 2007;1:236- 239)
Keywords: Tobacco smoking; Gingival crevicular fluid; Periodontal risk factor; Plaque index; Periodontal health